Pemanfaatan Perpustakaan Sebagai Pusat Sumber Belajar di SMP Negeri 46 Palembang - Azzahhra, Ayu; Salpiana, Choirunniswah; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the utilization of the library as a learning resource center at SMP Negeri 46 Palembang. The research is qualitative with a descriptive approach. The informants consisted of 15 people selected using purposive sampling. Data collection techniques included interviews, observations, and documentation. Data analysis was conducted through data collection, presentation, verification, and conclusion drawing. The results and discussion indicate that the utilization of the library as a learning resource center at SMP Negeri 46 Palembang has been implemented quite well, as evidenced by the relatively high frequency of student visits to the library, sufficient duration of library visits, and the variety of books read, which include not only textbooks but also other types of literature.